Increasing Halal Industry MSMEs in Gorontalo through Maqāṣid Asy-Syarī`ah - Rulyjanto Podungge; Rizal Darwis; Zumiyati S. Ibrahim; Arhjayati Rahim; A. Zamakhsyari Baharuddin; Syarifuddin (Asy-Syari'ah, 2025)
Micro, Small, and Medium Enterprises (MSMEs) are important in fostering economic development through broad-based community engagement, positioning this sector as a strategic priority for governments. The COVID-19 pandemic caused significant disruptions to the global economy, severely impacting MSMEs. Therefore, this study aimed to examine strategic measures to accelerate the growth and development of MSMEs in the halal industry in Gorontalo City. A field study method was adopted, and primary data were collected through observations, interviews, and documentation, complemented by secondary data from literature. The collected data were analysed using a qualitative descriptive method in the framework of business economics and Maqāṣid Asy-Syarī`ah principles. The results showed that both internal initiatives by MSMEs entrepreneurs and external support from governmental institutions synergise to provide essential moral and material reinforcement. These efforts were critical to the survival and growth of MSMEs and consistent with Maqāṣid Asy-Syarī`ah. Strengthening MSMEs represented a fundamental endeavour in ensuring sustainable economic resilience.